Proportion and time of day as a starting point for gauging gender differences of public transport use in Delhi. Issue 1 (March 2022) - Jain, Taru; Campbell, Morgan
Highlights: This paper contributes to both broad and specific discussions around gender and travel behavior in the global South. We focus on the "visibility" of women on Delhi's public transport system at various times of the day, illustrating that the proportion of women is always less than the proportion of men. We draw attention to how the presence of women on public transport declines rapidly as it becomes dark. econd, to illustrate a process of data collection on a modest research budget. Using a short intercept survey of women passengers, we highlight how issues of cost, comfort and safety impact travel decisions. The findings from this research are used to speak to the Delhi government's policy of making public transport free for all women in the city. Abstract: In this paper, we present new empirical data on the proportion of women and men using Delhi's public transport. In light of no publicly available data regarding bus and metro ridership in Delhi, this study illustrates a replicable process of data collection on a low budget to better understand the proportion of women travelling by public transport throughout the day. Understanding women's use of public transport contributes to the growing body of research addressing gendered travel in the global South and the specific safety concerns associated with Delhi. The research is pertitant to the Delhi government's proposed policy to make all public transport free for women. Data analysis reveals that throught the day, the proportion of women on buses ranges from 18 to 39 percent, while that on metro is from 26 and 42 percent. The proportion of women on the bus network reduces significantly after dark but this was not true for metro. Intercept surveys shed light on why this may be. These findings represent an important contribution to understanding why free public transport may improve women's mobility and greater visibility in the city. To conclude, we point to directions for future research.